Resistance characteristics of CTX-M type Shigella flexneri in China. Issue 9 (24th September 2019) - Bian, Fengzhi; Yao, Mingxiao; Fu, Hongmei; Yuan, Guangying; Wu, Shuzhi; Sun, Yuguo
Abstract : The present study was to identify the drug resistance, resistance mechanism and the extended-spectrum β-lactamase (ESBLs) genotypes of Shigella flexneri ( S. flexneri ) in Jinan. Susceptibility tests were performed by MIC-determination. The genotypes of β-lactamase were identified using PCR and DNA sequencing. The resistance transfer ability of the ESBL-producing strains was examined by conjugation tests. A total of 105 S. flexneri isolates were collected, and 34 (32.4%) were ESBL-producing isolates. All ESBL-producing isolates were susceptible to cefoxitin and imipenem, and 35.3% isolates were resistant to ciprofloxacin. ESBL-producing isolates showed high level resistant to ampicillin (100%), cefotaxime (100%), tetracycline (100%), chloramphenicol (100%), trimethoprim/sulfamethoxazole (100%), ceftazidime (73.5%) and cefepime (73.5%). Three types of β-lactamase genes ( bla TEM, bla OXA and bla CTX-M) were identified in all ESBL-producing isolates, and the genotypes were confirmed as bla TEM-1 (23/34), bla OXA-30 (34/34), bla CTX-M-14 (9/34) and bla CTX-M-15 (25/34) by sequencing. In conclusion, the Shigella strains isolated in Jinan are cross-resistant and multi-drug resistant. The main genotypes of ESBLs are CTX-M-14 and CTX-M-15.